2018
DOI: 10.1155/2018/5148085
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Urban Link Travel Time Distribution Using Markov Chains and Bayesian Approaches

Abstract: Despite the wide application of Floating Car Data (FCD) in urban link travel time and congestion estimation, the sparsity of observations from a low penetration rate of GPS-equipped floating cars make it difficult to estimate travel time distribution (TTD), especially when the travel times may have multimodal distributions that are associated with the underlying traffic states. In this case, the study develops a Bayesian approach based on particle filter framework for link TTD estimation using real-time and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Similarly, other researchers also divided traffic flow data into two parts. But then, they adopted two of the ARIMA model, the support vector machine, the generalized autoregressive conditional heteroscedasticity (GARCH) model and the Markov model to predict the two parts of traffic flow data [25][26][27][28][29][30]. To accurately capture the change rules of short-term traffic flow, Zhang et al [31] and Yang et al [32] divided traffic flow data into three parts, including the periodic trend, the deterministic part and the volatility part, and they pointed out that the volatility part is extremely important for short-term traffic flow prediction.…”
Section: Table 1 Summarization Of Single Methods Applied For Short-tmentioning
confidence: 99%
“…Similarly, other researchers also divided traffic flow data into two parts. But then, they adopted two of the ARIMA model, the support vector machine, the generalized autoregressive conditional heteroscedasticity (GARCH) model and the Markov model to predict the two parts of traffic flow data [25][26][27][28][29][30]. To accurately capture the change rules of short-term traffic flow, Zhang et al [31] and Yang et al [32] divided traffic flow data into three parts, including the periodic trend, the deterministic part and the volatility part, and they pointed out that the volatility part is extremely important for short-term traffic flow prediction.…”
Section: Table 1 Summarization Of Single Methods Applied For Short-tmentioning
confidence: 99%
“…It is clear from the determination results that, of all 52 periods, only 19 can yield the minimum sample size ranges from 5 to 14. However, it can still be observed that more samples in the range of [7,14] during peak periods are needed than those in the range of [5,10] during off-peak periods.…”
Section: Investigation Of the Minimum Sample Size Of Floating Carsmentioning
confidence: 99%
“…Probability distributions contain more information, such as percentiles, skewness and multimodality, that enable the monitoring of the varying characteristics of travel times on links ( 7 ). Recently, several attempts have been made to investigate the sample size necessary to ensure that the travel time observations generated from FCD can represent the link between TTDs and statistical reliability.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Traffic forecasting based on knowledge-driven methods mainly use queuing theory to simulate user behaviour [2] while data-driven approach for traffic congestion prediction are centred on time series-based models. Traditional time series methods as Auto-Regressive Integrated Moving Average (ARIMA) [3], Kalman filtering [4,5], principal component analysis [6], mixture models and Markov chain [7,8] may be applicable to predicting recurrent congestion as a process that is repetitive and periodic. Non-stationary effect however may not be easily captured through time series methods as well as spatial effects of congestion and they cannot mine the deep relationships between data.…”
Section: Introductionmentioning
confidence: 99%